2021
DOI: 10.1038/s41598-021-90171-0
|View full text |Cite
|
Sign up to set email alerts
|

Network-based analysis of key regulatory genes implicated in Type 2 Diabetes Mellitus and Recurrent Miscarriages in Turner Syndrome

Abstract: The information on the genotype–phenotype relationship in Turner Syndrome (TS) is inadequate because very few specific candidate genes are linked to its clinical features. We used the microarray data of TS to identify the key regulatory genes implicated with TS through a network approach. The causative factors of two common co-morbidities, Type 2 Diabetes Mellitus (T2DM) and Recurrent Miscarriages (RM), in the Turner population, are expected to be different from that of the general population. Through microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Several studies have demonstrated abnormal gene expression profiles ( 32 , 68 ) and differentially methylated X chr and autosomal genes in individuals with TS ( 68 , 69 ) Functional annotations of TS datasets (RNA sequencing and DNA methylation analysis of fibroblasts) demonstrate enrichment in genes involved in carbohydrate metabolism and glucose import ( 68 , 70 ). Two recent studies have employed bioinformatics approaches to identify differentially expressed genes in TS and used pathway analysis to determine key differentially regulated pathways relevant to diabetes ( 71 , 72 ). Candidate signature genes of DM in TS include 8 upregulated autosomal genes, including SLC29A2, THBS1, GPRC5B, CSHL1, ADAM22, IGHM, WIZ, IGHD , and 1 downregulated autosomal gene, COX11 ( 72 ).…”
Section: Clinical and Genetic Factors Involved In Hyperglycemia In Tsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated abnormal gene expression profiles ( 32 , 68 ) and differentially methylated X chr and autosomal genes in individuals with TS ( 68 , 69 ) Functional annotations of TS datasets (RNA sequencing and DNA methylation analysis of fibroblasts) demonstrate enrichment in genes involved in carbohydrate metabolism and glucose import ( 68 , 70 ). Two recent studies have employed bioinformatics approaches to identify differentially expressed genes in TS and used pathway analysis to determine key differentially regulated pathways relevant to diabetes ( 71 , 72 ). Candidate signature genes of DM in TS include 8 upregulated autosomal genes, including SLC29A2, THBS1, GPRC5B, CSHL1, ADAM22, IGHM, WIZ, IGHD , and 1 downregulated autosomal gene, COX11 ( 72 ).…”
Section: Clinical and Genetic Factors Involved In Hyperglycemia In Tsmentioning
confidence: 99%
“…Two recent studies have employed bioinformatics approaches to identify differentially expressed genes in TS and used pathway analysis to determine key differentially regulated pathways relevant to diabetes ( 71 , 72 ). Candidate signature genes of DM in TS include 8 upregulated autosomal genes, including SLC29A2, THBS1, GPRC5B, CSHL1, ADAM22, IGHM, WIZ, IGHD , and 1 downregulated autosomal gene, COX11 ( 72 ). It is not known if these altered autosomal genetic signatures are involved in the pathogenesis of diabetes in TS individuals.…”
Section: Clinical and Genetic Factors Involved In Hyperglycemia In Tsmentioning
confidence: 99%